Waste management in the meat processing industry: Conversion of paunch and DAF sludge into solid fuel. (February 2017) - Hamawand, Ihsan; Pittaway, Pam; Lewis, Larry; Chakrabarty, Sayan; Caldwell, Justin; Eberhard, Jochen; Chakraborty, Arpita
Highlights: Frying as a novelty method of managing wastes from meat processing industry. The oil content in the DAF sludge as frying medium. No or minimal additional oil may be required for the frying process. The manufactured high energy pellets is half the price of coal. The average estimated payback for investing in this process is 2.5 years. Abstract: This article addresses the novel dewatering process of immersion-frying of paunch and dissolved air flotation (DAF) sludge to produce high energy pellets. Literature have been analysed to address the feasibility of replacing conventional boiler fuel at meat processing facilities with high energy paunch-DAF sludge pellets (capsules). The value proposition of pelleting and frying this mixture into energy pellets is based on a Cost-Benefit Analysis (CBA). The CBA is based on information derived from the literature and consultation with the Australian Meat Processing Industry. The calorific properties of a mixture of paunch cake solids and DAF sludge were predicted from literature and industry consultation to validate the product. This study shows that the concept of pelletizing and frying paunch is economically feasible. The complete frying and dewatering of the paunch and DAF sludge mixture produces pellets with energy content per kilogram equivalent to coal. The estimated cost of this new product is half the price of coal and the payback period is estimated to be between 1.8 and 3.2 years. Further research is required for proof of concept, and to identify the technical challenges associated with integrating this technology into existing meat processing plants.